La inseguridad jurídica procesal como consecuencia de la intervención de peritos no especializados en la escena de los hechos. - ORDOÑEZ ORDOÑEZ, RICHARD VICENTE (2011)
As for the problem outlined in this work of investigation juridical partner, with regard to the lack of personal with specialization that acts as expert inside the investigation of the scene of the facts, this dedicated to cover that respective hole that although it is named in the code of penal procedure personnel's intervention specialized in the investigation of the scene of the facts, this is not completed residing here in if the flaw of the judicial system resided in that if there is not specialized personnel the gathered tests they would not serve since in any moment they would be contaminated or as he/she tells it the theory of the fruit of the serious poisoned tree the result of the bad or incorrectly obtained test corrupting this way of nullity the process. This way when analyzing the Code of penal procedure and respective regulations can reach the conclusion that in the moment of application of this norm in which specialized personnel's intervention is required is not completed since soon after the interpretation that you taking of that if there is not specialized personnel he/she took the person with more experience or of spotless behaviour, leaving without truthfulness or credibility that that this he/she can carry out as investigator. That is to say if we base ourselves on this like we can trust a spotless justice or in the right that guarantees us the constitution and international organisms to the application of a justice without restrictions and with the biggest security that this he/she can lend us in the development or resolution of the processes.